Properties of tubes from Zr-1% Nb alloy after thermochemical treatment and hydrogenation - Trush, V.S.; Voyevodin, V.N.; Stoev, P.I.; Fedirko, V.N.; Lukyanenko, A.G.; Tikhonovsky, M.A.; Panov, V.A. (Вопросы атомной науки и техники, 2021)
The influence of treatment in controlled gas environments with subsequent hydrogenation on the physical and mechanical characteristics of the Zr-1% Nb zirconium alloy has been investigated. The surface hardness and the size of the diffusion-hardened layer of the ring-samples cut from fuel tubes from the Zr-1% Nb alloy after treatment in oxygen- and nitrogen-containing gaseous media with subsequent saturation with hydrogen have been established. The influence of the parameters of the gaseous medium and the modes of thermochemical treatment (TCT) of specimens-rings on the destructive stresses under static load at temperatures of 20 and 380 °C is shown. It was revealed that treatment in the investigated gas environment increases the resistance to hydrogen saturation and has a positive effect on the long-term strength of ring specimens from the zirconium alloy Zr-1% Nb. Досліджено вплив термохімічної обробки в контрольованих газових середовищах з наступним насиченням воднем на фізико-механічні характеристики цирконієвого сплаву Zr-1% Nb. Визначено твердість поверхні і розмір дифузійно-зміцненого шару зразків-кілець, вирізаних з твельних трубок сплаву Zr-1% Nb після обробки в кисне- і азотовмісних газових середовищах, а також з наступним насиченням воднем. Показано вплив параметрів газового середовища і режимів термохімічної обробки зразків-кілець на руйнівні напруження за статичного тривалого навантаження за температурах 20 і 380 °С. Виявлено, що обробка в дослідженому газовому середовищі підвищує опірність насиченню воднем і позитивно впливає на тривалу міцність зразків-кілець з цирконієвого сплаву Zr-1% Nb. Исследовано влияние термохимической обработки в контролируемых газовых средах с последующим наводороживанием на физико-механические характеристики циркониевого сплава Zr-1% Nb. Установлены твердость поверхности и размер диффузионно-упрочненного слоя образцов-колец, вырезанных из твэльных трубок из сплава Zr-1% Nb после обработки в кислород- и азотсодержащих газовых средах с последующим насыщением водородом. Показаны влияния параметров газовой среды и режимов термохимической обработки образцов-колец на напряжения разрушения при статической нагрузке при температурах 20 и 380 °С. Выявлено, что обработка в исследованных газовых средах повышает сопротивляемость насыщению водородом и положительно влияет на длительную прочность образцов-колец из циркониевого сплава Zr-1% Nb.